Cross-cultural adaptation and psychometric properties of the Brazilian coach-athlete relationship questionnaire (CART-Q) - Athlete Version - Lenamar Fiorese Vieira; José Roberto Andrade do Nascimento Junior; Constanza Pujals; Sophia Jowett; Renan Codonhato; João Ricardo Nickenig Vissoci (Universidade Federal de Santa Catarina, 2015)
The aim of this study was to test the psychometric properties of the Brazilian version of the Coach-Athlete Relationship Questionnaire (CART-Q) - Athlete Version. For this, three studies were performed. In the first, four translators and five experts in Sport Psychology adapted the CART-Q contents to the Brazilian context. In the second, 364 athletes of individual and collective sports answered the adapted version of CART-Q. In the third, an independent sample of 185 athletes answered the CART-Q and the Task and Ego Orientation in Sport Questionnaire (TEOSQ) to analyze the external validity of the instrument; and 50 athletes answered the CART-Q in two distinct moments for the analysis of the temporal stability. Study 1 showed that the Portuguese version contains clear and relevant questions (CVC> 0.80). Study 2 showed that the CART-Q presents satisfactory internal consistency (α> 0.70 / CC> 0.70). The confirmatory factor analysis showed that the model with 11 items showed good fit [X2/gl = 3.03; CFI = 0.96, GFI = 0.94; TLI = 0.94; RMSEA = 0.08] and also the existence of the second-order model. Study 3 showed the external (r> 0.40 with variable task orientation) and internal validity (CFA with an independent sample) and temporal stability (ICC> 0.70). It was concluded that the Brazilian version for of CART-Q proved to be valid to evaluate the perception of athletes about their relationship with the coach in the Brazilian sports context.